The lived neighborhood: understanding how people with dementia engage with their local environment. (2nd May 2017) - Ward, Richard; Clark, Andrew; Campbell, Sarah; Graham, Barbara; Kullberg, Agneta; Manji, Kainde; Rummery, Kirstein; Keady, John
ABSTRACT: Background: In this paper, we report progress on "Neighborhoods: our people, our places" an international study about how people living with dementia interact with their neighborhoods. The ideas of social health and citizenship are drawn upon to contextualize the data and make a case for recognizing and understanding the strengths and agency of people with dementia. In particular, we address the lived experience of the environment as a route to better understanding the capabilities, capacities, and competencies of people living with dementia. In doing this, our aim is to demonstrate the contribution of social engagement and environmental support to social health. Methods: The study aims to "map" local spaces and networks across three field sites (Manchester, Central Scotland and Linkoping, Sweden). It employs a mix of qualitative and participatory approaches that include mobile and visual methods intended to create knowledge that will inform the design and piloting of a neighborhood-based intervention. Results: Our research shows that the neighborhood plays an active role in the lives of people with dementia, setting limits, and constraints but also offering significant opportunities, encompassing forms of help and support as yet rarely discussed in the field of dementia studies. The paper presents new and distinctive insights into the relationship between neighborhoods and everyday life for people with dementia that have important implications for the debate on social health and policy concerning dementia friendly communities. Conclusion: We end by reflecting on the messages for policy and practice that are beginning to emerge from this on-going study.